Analyzing the Efficiency and Loan Loss Provisioning of the Banks in Hong Kong - Chan, Hiu Man (2013)
This study examines the efficiency and determinants of loan loss provisions by using data from 19 commercial banks in Hong Kong over the period 2006-2011. Distinct from previous studies, we conduct a two-stage analysis, in the first stage X-efficiency is estimated and then included in the second stage for the estimation of determinants of loan loss provisions using system GMM estimation method. In particular, we examine the income smoothing and capital management hypothesis, the relationship between loan loss provisions and the business cycle (i.e. pro-cyclicality and counter-cyclicality) as well as the effect of X-efficiency on loan loss provisioning.